Dream Treatment: On Sitting Down to Read a Letter from Freud. Issue 3 (November 2017) - Royle, Nicholas
Abstract : This text seeks to analyse a dream in which Freud writes to the author. Particular attention is given to the notion of treatment and, in a memorable phrase from Hélène Cixous, 'how to treat the dream as a dream'. Royle draws on diverse references (Donald Trump, Hugh Laurie, Howard Jacobson, Wallace Stevens, Jacques Derrida and Cixous), and focuses on a range of Freud's writings (a letter to Thomas Mann, The Interpretation of Dreams, 'A Disturbance of Memory on the Acropolis' and 'A Note on the Unconscious in Psychoanalysis'), in order to explore the relationship between psychoanalysis and literature. Particular attention is given to free association, deferred effect and the epistolary.